Time Token Arends 1998 as a Technique to Teach Speaking Factual Report Text to the Students of Ninth Grade of SMPN 3 Peterongan (RETAIN, 2016)
Time Token Arends 1998 as a Technique to Teach Speaking Factual Report Text to the Students of Ninth Grade of SMPN 3 Peterongan Dewidya Isna Safitri English Education, Language and Art Faculty, State University Surabaya dewidyasafitri@mhs.unesa.ac.id Ririn Pusparini, S.Pd., M.Pd. English Education, Language and Art Faculty, State University of Surabaya rrn.puspa@gmail.com Abstrak Kemampuan berbicara dipertimbangkan sebagai salah satu kemampuan dasar yang penting untuk diajarkan di sekolah. Mengajarkan kemampuan berbicara bertujuan untuk memfasilitasi pelajar dengan kemampuan berkomunikasi dan aktivitas kelas yang mengembangkan kemampuan siswa untuk mengekspresikan diri mereka melalui perkataan (Richard, 2005:2). Menteri Pendidikan dan Kebudayaan mengajukan sebuah kemampuan dasar untuk membuat siswa dapat menyampaikan teks factual report, hal tersebut berguna untuk mencapai tujuan yang dimaksud,. Oleh karena itu, guru di SMPN 3 Peterongan menggunakan Time Token Arends 1998 sebagai salah satu teknik untuk mengajar teks factual report.Time Token Arends dapat membantu guru untuk menghindari pendominasian berbicara dan beberapa siswa yang memilih pasif di kelas (Istarani in Sukmayati, 2014:38). Seluruh siswa akan mendapatkan kesempatan yang sama untuk berbicara di depan kelas. Oleh sebab itu, penilitian ini bertujuan untuk mendeskripsikan pengimplementasian Time Token Arend 1998 dalam mengajarkan kemampuan berbicara teks factual report pada siswa kelas 9 di SMPN 3 Peterongan, penampilan siswa ketika berbicara dan respon siswa terhadap pengimplementasian Time Token Arends. Penelitian ini dideskripsikan dengan cara kualitatif. Ada tiga rumusan masalah yang telah dibuat oleh peneliti. Rumusan masalah tersebut mempertanyakan bagaimana guru mengimplementasikan Time Token Arends untuk mengajarkan kemampuan berbicara siswa kelas 9 di SMPN 3 Peterongan dalam menyampaikan teks factual report, bagaimana kemampuan berbicara siswa kelas 9 di SMPN 3 Peterongan dalam menyampaikan teks factual report dan bagaimanakah respon siswa terhadap pengimplementasian teknik mengajar tersebut. Hasil penelitian ini menyatakan bahwa guru mengimplementasikan Time Token Arends 1998 dalam pengajaran penyampaian teks factual report dengan baik dan membuat siswa menjadi aktif untuk berbicara di kelas. Tidak ada siswa yang mendominasi di kelas atau siswa yang memilih untuk terus diam selama pengimplementasian Time Token Arends. Selain itu, teknik ini juga menarik dan dapat mendorong siswa untuk lebih aktif. Dapat disimpulkan bahwa Time Token Arends 1998 dapat digunakan untuk mengajar kemampuan berbicara siswa kelas 9 terlebih lagi untuk penyampaian teks factual report. Oleh karena itu, peneliti Guru Bahasa Inggris dapat menggunakan Time Token Arend sebagai salah satu variasi teknik pengajaran. Kata Kunci : Time Token Arends 1998, Kemampuan Berbicara, Teks Factual Report Abstract Speaking is considered as one of the basic skills that is important to be taught in the school. Teaching speaking is aimed provide learners with communicative competence and classroom activities that develop learners ability to express themselves through speeches ( Richard, 2005:2). In order to achieve the goal, the ministry of education proposes a basic competence to get the students being able to deliver factual report text. Thus, the teacher uses Time Token Arends 1998 as a technique to teach speaking factual report text. Time Token Arends 1998 can help the teacher to avoid talking domination and students’ silence (Istarani in Sukmayati, 2014:38). All of the students will get the same chances to speak in front of the class. Therefore, this researcher is aimed to describe the implementation of time token Arend 1998 in teaching speaking factual report to the ninth graders of SMPN 3 Peterongan, the students’ speaking performance and students’ response toward the implementation of the technique. This research is described in qualitative way. Three research questions which had been formulated by the writer were how the teacher implements Time Token Arends 1998 for teaching speaking factual report text to the ninth graders of SMPN 3 Peterongan, how the students’ speaking ability in delivering factual report text toward the implementation of Time Token Arends 1998 in teaching speaking factual report text to the ninth graders of SMPN 3 Peterongan and how are the students’ responses during the implementation of Time Token Arends 1998 in teaching speaking factual report text to the ninth graders of SMPN 3 Peterongan. The researcher used observation checklist, students’ speaking task and questionnaire as instruments to help her gaining the data. The result showed that the teacher implemented Time Token Arends 1998 in teaching speaking factual report text well and made the students to be active to speak in class. There were no students’ talking domination and students’ silence during the implementation. In addition, this technique is interesting and able to encourage the students to be active. It can be concluded that time token Arends 1998 could be used in the teaching speaking factual report text for the ninth graders. Therefore, the researcher suggests English teachers to use Time Token Arends as one of the various techniques. Key Words : Time Token Arends 1998, Speaking Skill, Factual Report Text